Mild-temperature photothermal assisted CuSi nanowires for promoting infected wound healing - Feng, Yanping; Wu, Mingzhen; Zhang, Haidong; Xu, He; Li, Huili; Chen, Dongmin; Jiang, Hongyi; Chang, Jiang; Dong, Zhihong; Yang, Chen (Frontiers in Bioengineering and Biotechnology, 2023)
In clinical practice, the utilization of antibiotics is still the main approach for the treatment of wound contamination, which lacks the ability to accelerate wound healing and arises the global concern of antimicrobial resistance. Plenty of alternative methods have been explored in recent years due to the fast development of material science. Here, CuO/SiO2 nanowires (CuSi NWs) with good near-infrared (NIR) photothermal conversion ability are synthesized by a one-step hydrothermal method. The as-prepared CuSi NWs possess excellent antibacterial ability against both Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus), which could be enhanced by the assistance of mild photothermal therapy (PTT). Moreover, CuSi NWs at suitable concentrations can promote proliferation, migration, and angiogenic gene expression of human umbilical vein endothelial cells (HUVECs), exhibiting a remarkable pro-vascularization ability. The in vivo mouse infect model further proves that the CuSi NWs might be a good candidate for the treatment of infected wounds as the high antibacterial efficiency and accelerated wound healing is obtained.